PERMAINAN TRADISIONAL SEBAGAI SARANA STIMULASI PERKEMBANGAN PADA ANAK USIA DINI - Mahmud, Bonita (Institut Agama Islam Negeri Bone, 2019)
The technology development has an impact on children's habits who spend more time on gadgets or television.Â Children play more modern games than traditional games. This condition has an impact on the development of children who experience varied obstacles because children spend more time playing online games than playing games by moving their bodies. Parents and educators can use traditional games as a means of stimulating the development of children.Â Traditional games are adapted to the local context of the child. The research method in this paper uses the literature review approach.Keywords: Traditional games, development of childrenÂ